Increased Coherence of White Matter Fiber Tract Organization in Adults with Asperger Syndrome: A Diffusion Tensor Imaging Study. Issue 6 (2nd October 2013) - Roine, Ulrika; Roine, Timo; Salmi, Juha; Nieminen‐Von Wendt, Taina; Leppämäki, Sami; Rintahaka, Pertti; Tani, Pekka; Leemans, Alexander; Sams, Mikko
<x xml:space="preserve">Abstract</x> To investigate whether there are global white matter (WM) differences between autistic and healthy adults, we performed diffusion tensor imaging (DTI) in 14 male adults with Asperger syndrome (AS) and 19 gender‐, age‐, and intelligence quotient‐matched controls. We focused on individuals with high‐functioning autism spectrum disorder (ASD), AS, to decrease heterogeneity caused by large variation in the cognitive profile. Previous DTI studies of ASD have mainly focused on finding local changes in fractional anisotropy (FA) and mean diffusivity (MD), two indexes used to characterize microstructural properties of WM. Although the local or voxel‐based approaches may be able to provide detailed information in terms of location of the observed differences, such results are known to be highly sensitive to partial volume effects, registration errors, or placement of the regions of interest. Therefore, we performed global histogram analyses of (a) whole‐brain tractography results and (b) skeletonized WM masks. In addition to the FA and MD, the planar diffusion coefficient (CP) was computed as it can provide more specific information of the complexity of the neural structure. Our main finding indicated that adults with AS had higher mean FA values than controls. A less complex neural structure in adults with AS could have explained the results, but no significant difference in CP was found. Our results suggest that there are global abnormalities in the WM tissue of adults with AS. Autism Res 2013, 6: 642–650. © 2013 International Society for Autism Research, Wiley Periodicals, Inc.